The Influence of Financial Literacy, Fear of Missing Out (FoMO), and E-Wallet Use on Student Financial Behavior (A Case Study of Accounting Students from the 2021-2024 Cohort at Jambi University) - Rahmadina; Muhkzarudfa; Muhammad Gowon (Greenation International Journal of Economics and Accounting, 2025)
This study aims to analyze the influence of financial literacy, the Fear of Missing Out (FoMO) phenomenon, and the use of e-wallets on the financial behavior of students. This study was conducted on students of the Accounting Study Program at the University of Jambi from the 2021–2024 batch. Background: The younger generation, especially students, has the potential to influence their consumption patterns and financial decision-making. A quantitative approach was used in this study with a survey method and questionnaire distribution to respondents who were determined through purposive sampling. The collected data were analyzed using multiple linear regression to test the influence of independent variables on dependent variables.